THE URBAN PLANNING CONCEPT BASED ON SMART CITY APPROACH - Bakri, Muhammad; Kasim, Anita Ahmad (Trijurnal, Research Institution, Trisakti University, 2018)
Smart City is considered as a strategy to reduce the problem due to the rapid urban growth and urbanization. From the review of previous reported studies, it is resolved that smart city has provided various different perspectives. In order to understand smart city from the context of urban planning, it is essential to recognize the considerable aspects which is important from both sides. This article comprises the result of literature review from the related studies resulting on the development of a diagrammatical model figuring the summary of those studies. Keywords: Smart city, Urban Planning, a diagrammatical model.